Mendidik Dengan Model Komunikasi Al Quran: Analisis Term Komunikasi dalam Al Quran dan Impelemetasinya pada Proses Belajar Mengajar - Achmad Anwar Abidin (Proceedings of Annual Conference for Muslim Scholars, 2017)
Communication is also becoming one of the factors that influence the success of an educational process for the success indicator is the achievement of a goal of learning or educational purpose itself is by tersampaikannya message in this case the learning material to learners through an effective communication. According Onong Uchjana Efendy, in terms of the process, education is communication within the meaning of the word that in the process the two components consisting of the person, that teacher as learner as a communicator and communicant. Communication models in the Qur'an is a communication model that should serve as an example and can be practiced in everyday life of Muslims, especially for educators every day in direct contact with the process of learning, both formal, non-formal or informal.Dalam the learning process of a teacher is also expected to implement the model qâulan balighâ communication (speech which imprint hearts), qâulan layyina (word meek), qâulan ma'rufa (a good word again firmly), qâulan maysura (speech which deserved), qâulan Karima (words that glorify ) and is able to give mauidhah (teaching), Nashihah (advice), da'wah (invitation) and taushiyah (edify each).Keywords; Education, model of communications, learning.